Araucariaceae macrofossil record from South America and Antarctica - Panti, Carolina (2012)
Araucariaceae fossils are abundant in Patagonia and on Seymour (Marambio) and King George (25 de Mayo) islands, Antarctica. Araucariacean macrofossil suites are represented by records of 121 woods, leaves, ovuliferous scales, cones, one seed and seedlings, many of them placed in 50 formalized morphospecies. Although Araucariaceae fossil pollen is known since the Triassic, the oldest reliable macrofossil records in South America and Antarctica are from the Early Jurassic. In the Early Cretaceous, the family reached its widest distribution, with records from northern South America (cones and leaves from Colombia and Brazil). In the Late Cretaceous, the abundance of Araucariaceae began to decline. In the Cenozoic, all the fossils are derived from Patagonia and Antarctica, and this probably reflects a genuine contraction in the family's distribution.